Which of the following equations is not equivalent to the others?

y = -4 + 3 x
y = -3 x + (-4)
y = -3 x - 4
y = -4 - 3 x

Respuesta :

gmany

Answer:

y = -4 + 3x

Step-by-step explanation:

Let's write the terms:

y = -4 + 3x → (-4) and (3x)

y = -3x + (-4) → (-4) and (-3x)

y = -3x - 4 → (-4) and (-3x)

y = -4 - 3x → (-4) and (-3x)

Other method

1. y = -4 + 3x

2. y = -3x + (-4) = -3x - 4 → 3.     use (-)(+) = (-)

3. y = -3x - 4

4. y = -4 - 3x = -4 + (-3x) = (-3x) + (-4) = -3x - 4 → 3.  use commutative property

Answer:

y = -4 + 3x

*Explanation*

because math

ACCESS MORE